OPTIMIZING EDUCATIONAL ASPIRATIONS: THE INFLUENCE OF LEARNING MOTIVATION AND SELF-POTENTIAL ON HIGHER EDUCATION INTEREST - Rinjani, Rizki Amelia; Sumiati, Ati; Adha, Maulana Amirul (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
The interest of vocational high school students to continue their education to college is still relatively low. This study aims to determine the effect of learning motivation and self-potential on the interest in continuing their education to college in grade XII students at public vocational high schools in East Jakarta, Indonesia. This study uses a quantitative approach with a survey method. The research sample was taken using the proportional random sampling technique with the Slovin formula, resulting in 105 samples. Data collection was carried out using a questionnaire using a Likert scale. The data analysis techniques used were normality test, linearity test, multicollinearity test, heteroscedasticity test, and multiple regression analysis test. The results showed that learning motivation had a positive and significant effect on the interest in continuing their education to college. Self-potential had a positive and significant effect on the interest in continuing their education to college, and learning motivation and self-potential together had a positive effect on the interest in continuing their education to college, this shows that the higher the learning motivation and self-potential, the greater the possibility of students having an interest in continuing their education to college.